2014
DOI: 10.1155/2014/953509
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Prognostic Factors of Epithelial Ovarian Carcinoma

Abstract: Ovarian cancer remains the most common cause of gynecologic cancer-related death among women in developed countries. Nevertheless, subgroups of ovarian cancer patients experience relatively longer survival. Efforts to identify prognostic factors that characterize such patients are ongoing, with investigational areas including tumor characteristics, surgical management, inheritance patterns, immunologic factors, and genomic patterns. This review discusses various demographic, clinical, and molecular factors imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 110 publications
1
44
1
1
Order By: Relevance
“…Among these, high-grade serous ovarian cancers (HGSOCs) are the most prevalent representing 80-85% and display the highest mortality rates [2]. Several prognostic factors have been proposed for HGSOC, including: stage, quality of debulking surgery, and response to chemotherapy [3,4], however only a few of them have been demonstrated clinically relevant [5].…”
mentioning
confidence: 99%
“…Among these, high-grade serous ovarian cancers (HGSOCs) are the most prevalent representing 80-85% and display the highest mortality rates [2]. Several prognostic factors have been proposed for HGSOC, including: stage, quality of debulking surgery, and response to chemotherapy [3,4], however only a few of them have been demonstrated clinically relevant [5].…”
mentioning
confidence: 99%
“…Kanker ovarium paling banyak adalah tipe epitel, dimana 70% pasien datang sudah dalam stadium lanjut, dengan angka ketahanan hidup 10 tahun sekitar 15-30%; sedangkan angka ketahanan hidup untuk stadium awal adalah lebih dari 90%. 4 Kanker ovarium tipe epitel merupakan penyakit heterogen dengan berbagai subtipe histologi (histotipe) yang berbeda dalam asal sel, patogenesis, perubahan molekuler, ekspresi gen, dan prognosis. Secara histologis, WHO mengklasifikasikan tumor ovarium tipe epitel menjadi tipe serosa, musinosa, endometrioid, clear cell, seromusin, brenner dan karsinoma yang tidak terdiferensiasi.…”
Section: Pendahuluanunclassified
“…In a recent study, different factors found associated with the prognosis of EOC include patient's age, performance status, tumor stage and ascites, tumor grade, histopathologic subtype, obesity, surgical de-bulking, expression of genes (CYP4B1, CEPT1, CHMP4A), and immunological factors [21] .…”
Section: Prognosismentioning
confidence: 99%
“…Antibody therapy, immune checkpoint inhibitors, vaccine strategies, adoptive cell therapy, and combinatorial immunotherapy are all used for the treatment of the disease [16] . There are numerous review papers discussing ovarian carcinoma's origin and its development [17] , types and subtypes [13,18] , diagnosis [19,20] , prognosis [21] , and treatment [16,[22][23][24] . As such, there is a need to review and update existing information on ovarian carcinoma.…”
Section: Introductionmentioning
confidence: 99%